El enclave minero y el desmejoramiento de los niveles de vida de los pueblos de la cuenca alta del rió Rimac - Ramirez Bautista, Bernardino (2005)
the study presents the analysis of the antagonistic relation between the mining companies and the municipalities and mining workers of the high river basin of the rimac river; of miners Yauliyacu and Casapalca , their more excellent aspects, investments, production, labor force as well as the social conditions of the surroundings appear in which they operate. Of the communities social and economic, San Antonio, San Mateo de Huanchor and Chicla, his organization, her aspects, the conditions of life its population, as well as its relations with the permanet municipalities and their complanings before the company. the paper of the State in relation to the mining operation in the zone is also analyzed